Behavioral Predisposing Factors in Mothers of Toddlers Affecting the Risk of Stunting Among Toddlers in Dairi Regency - Samsider Sitorus; Juliani Purba; Haripin Togap Sinaga; Apriska Dewi Sipayung (Postgraduate, University of Mataram, 2024)
Stunting a significant public health issue worldwide, particularly in low- and middle-income countries where access to adequate nutrition and healthcare is limited. This condition affects not only physical growth but also cognitive development and well-being. The study aimed to explore the impact of maternal behavioral factors, including nutrition, breastfeeding practices, and health-seeking behaviors, on the risk of stunting among toddlers. Method It is a cross sectional study with retrospective case control approach. A total of 120 mothers who had toddlers aged 6-24 months involved recruited from Puskesmas Pegagan Julu, Dairi District. Variables collected were knowledge, attitude and action of mothers, weight, height, age of children and exclusive breastfeeding consumption. Analyzed was performed through bivariate and multivariate logistic regression. Results a total 28.60% of toddlers were stunted, with significant links found between maternal nutritional knowledge (OR = 0.45, p < 0.05), exclusive breastfeeding for six months (OR = 0.60, p < 0.05), and regular health-seeking behavior (OR = 0.32, p < 0.01), and reduced stunting risk. Conversely, inadequate sanitation facilities were associated with increased stunting prevalence (OR = 2.76, p < 0.01).